2023
DOI: 10.3390/biomedicines11020567
|View full text |Cite
|
Sign up to set email alerts
|

Urate Transporter 1 Can Be a Therapeutic Target Molecule for Chronic Kidney Disease and Diabetic Kidney Disease: A Retrospective Longitudinal Study

Abstract: Chronic kidney disease (CKD) is a major global health problem for which there are no curative drug treatments. Hyperuricemia is one of risk factors for CKD. The evidence on effects of uric acid (UA)-lowering treatments on the progression of CKD was very limited and previous meta-analyses used only trials which primarily used xanthin oxidase (XO) inhibitors because the reports on fulminant hepatitis due to benzbromarone kept us from using uricosuric agents for hyperuricemia patients. Dotinurad, a novel selectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 53 publications
3
12
0
Order By: Relevance
“…The beneficial in vivo effects of dotinurad in terms of ameliorating the cardiac remodeling and function could also be indirectly mediated by the action of dotinurad on other tissues, such as the kidney. 20 However, at least, plasma Cr levels were comparable between HFD and NFD, and dotinurad treatment did not affect them ( Figure S2 ), consistent with our previous study. 21 …”
Section: Resultssupporting
confidence: 90%
“…The beneficial in vivo effects of dotinurad in terms of ameliorating the cardiac remodeling and function could also be indirectly mediated by the action of dotinurad on other tissues, such as the kidney. 20 However, at least, plasma Cr levels were comparable between HFD and NFD, and dotinurad treatment did not affect them ( Figure S2 ), consistent with our previous study. 21 …”
Section: Resultssupporting
confidence: 90%
“…This exquisite crosstalk between URAT1 and ABCG2 induced by dotinurad may be beneficially associated with the development and progression of CKD. Our recent study showed that dotinurad reduced urinary albumin creatinine ratio (UACR) and increased eGFR in patients with CKD [11], supporting our hypothesis. Dotinurad does not inhibit OAT1/3, and then does not increase plasma IS [7].…”
Section: To the Editorsupporting
confidence: 79%
“…In this case, an improvement in albuminuria after the start of dotinurad was also observed [ 79 ]. In our study, the 6-month dotinurad treatment improved albuminuria and eGFR in hyperuricemic patients [ 14 ]. In another study, although eGFR did not significantly change in patients whose eGFR was 30 or more, dotinurad significantly improved the eGFR in patients whose eGFR was less than 30 [ 80 ].…”
Section: The Association Of Urat1 and Other Ua Transporters With Ckdmentioning
confidence: 99%
“…We found that dotinurad reduced body weight, blood pressure, HbA1c, serum low-density lipoprotein-cholesterol (LDL-C), triglyceride (TG), and non-high-density lipoprotein-cholesterol (non-HDL-C), as well as serum UA, in patients with CKD and DKD [ 14 ]. To our knowledge, our study is the first to report such metabolic effects of dotinurad.…”
Section: The Association Of Urat1 and Other Ua Transporters With Meta...mentioning
confidence: 99%
See 1 more Smart Citation